Combined approach of multiloculated hydrocephalus and isolated fourth ventricle - Lucas de Souza Rodrigues dos Santos; Leo Gordiano Matias; Fernando Luís Maeda; Humberto Belem de Aquino; Enrico Ghizoni (Brazilian Society for Pediatric Neurosurgery, 2020)
A female newborn patient presents with meningitis and hydrocephalus after lumbosacral myelomeningocele repair and skin closure. An external ventricular drain was used during the meningitis treatment. Patient had a late onset multiloculated hydrocephalus and isolated fourth ventricle on CT scan follow-up. We performed combined approach with a craniotomy, dissection of intraparietal sulcus entering in the atrium of left lateral ventricle and used endoscopic assistance to fenestrate intraventricular septations and to put a ventricular catheter through tentorium to drain both supra and infratentorial ventricles. The patient improved clinically and radiologically.